Optimal Topology Configuration Design of Contoured-Beam Mesh Reflectors - Guigeng Yang; Aofei Tang; Yiqun Zhang; Zhenyi Yuan; Lingfei Kong (International Journal of Antennas and Propagation)
It is significant for the practical application of space-borne mesh-shaped reflectors to reduce the structural complexity under the condition of the far-field electromagnetic (EM) performance being satisfied. To address this problem, an optimal topology configuration design method is proposed for the mesh-shaped reflectors. First, a multifrequency optimization model is established to obtain the mesh-shaped reflector. The reflector nodal deviations in the x-, y-, and z-directions are simultaneously selected as design variables to design the shape of the mesh reflector and realize the required contoured beams within the whole frequency band. Then, based on the multifrequency optimization model, an iterative design technology is proposed to obtain the optimal topology configuration of the mesh-shaped reflector. Finally, a typical example of a mesh reflector with contoured beams covering the continental United States (CONUS) is investigated to demonstrate the feasibility of the method.